Gulliver's travels an annotated text with critical essays - Swift, Jonathan, 1667-1745. (New York Norton, 1961)
The voyages of an Englishman carry him to such strange places as Lilliput, a land of people six inches high, Brobdingnag, a land of giants, and Glubbdubdrib, an island of sorcerers.
Bibliography: p. 358-361.
2
Keywords: English fiction